Benefit of burosumab in adults with X-linked hypophosphataemia (XLH) is maintained with long-term treatment. Issue 1 (28th February 2023) - Kamenicky, Peter; Briot, Karine; Brandi, Maria Luisa; Cohen-Solal, Martine; Crowley, Rachel K; Keen, Richard; Kolta, Sami; Lachmann, Robin H; Lecoq, Anne-Lise; Ralston, Stuart H; Walsh, Jennifer S; Rylands, Angela J; et al.
Abstract : Objectives: To report the impact of continued burosumab treatment on clinical laboratory tests of efficacy, patient-reported outcomes (PROs) and ambulatory function in adults with X-linked hypophosphataemia who continued from a 96-week phase 3 study into a 48-week open-label extension. Methods: Eligible participants from the phase 3 study continued on the burosumab regimen received at the end of the phase 3 study for a further 48 weeks (n=31). Some (not all) received compassionate burosumab treatment between the two studies (a period of 6–18 months). The primary efficacy outcome was fasting serum phosphate concentration; secondary outcomes were serum 1, 25 dihydroxyvitamin D concentration, renal phosphate reabsorption, PROs and ambulatory function. Results: Improvements in fasting serum phosphate, serum 1, 25 dihydroxyvitamin D and renal phosphate reabsorption at 96 weeks were maintained through the 48-week extension. Improvements were also maintained in stiffness and physical function measured using the Western Ontario and McMaster Universities Osteoarthritis Index, pain and fatigue endpoints measuring using the Brief Pain Inventory short-form and Brief Pain Inventory, respectively, and in ambulatory function (6-Minute Walk Test). A post-hoc exploratory analysis exploring outcomes in participants who discontinued burosumab treatment between the studies (n=7) and those who received at least one dose (n=23) indicated that the benefits of burosumab on clinical laboratory tests of efficacy, PROs and ambulatory function may be lost when treatment is interrupted but recover over time when treatment is reinstated. Conclusion: Continued treatment with burosumab appears necessary for sustained clinical benefit. Trial registration numbers: Phase 3: NCT02526160 ; open-label extension: NCT03920072 .